CONSTRUCTION OF THE VECTOR OF MINIMUM WORKS FOR THE PERFORMANCE OF THE SCHEDULED TASKS OF THE OPERATIONAL AND DISPATCH MANAGEMENT OF THE TECHNOLOGICAL COMPLEX - Shukhrat Manapovich, Gulyamov; Barnokhon Maratovna, Temerbekova (International Journal of Psychosocial Rehabilitation, 2020)
The properties of the noise immunity assessment for each mine vector are analyzed, which, using the constructed estimate, can determine the minimum mine vector that provides the same results as the complex and has the same noise immunity rating as this vector but has the lowest mine values. The properties of the noise immunity criterion for the implementation of a chemical-technological complex with a complex structure are generalized. It is proved that the properties of the introduced noise immunity assessment allow it to be used as an optimality criterion in the formulation and solution of problems of compensation for losses from disturbances in systems of operational dispatch control of chemical-technological complexes with a continuous nature of production.